Interplay between BRCA1 and RHAMM regulates epithelial apicobasal polarization and may influence risk of creast cancer - Maxwell, Chris; Hamann, Ute; Sutter, Christian (PLoS biology, 2011)
Genetic analysis identifies the HMMR gene as a modifier of the breast cancer risk associated with BRCA1 gene mutation, while cell biological analysis of the protein product suggests a function in regulating development of the mammary gland.